HUBUNGAN PERAN SERTA KADER POSYANDU DENGAN PERAWATAN HIPERTENSI PADA LANJUT USIA (LANSIA) DI DESA SALAMREJO SENTOLO KULON PROGO - Sugiyanto (MEDIA ILMU KESEHATAN, 2016)
Background: One of the most prevalent cardiovascular problems in elderly people is hypertension.Health cadres are those who voluntarily dedicate their time to have concern about elderly people’s health status in the community. Health cadres’ roles are important to promote elderly people quality of life, including their hypertension management. Objectives: This research aimed to analyzethe correlation between the role of health cadres of elderly posyandu and the treatment of hypertension at Salamrejo Village Sentolo Kulon Progo. Methods: This research was a correlational study with a cross sectional approach. The sample of this study was selectedwith a total sampling technique, drawn 57 hypertension patients. Data were analyzedwith Spearman rank correlation. Results:The result showed that coefficient correlation value of Spearman’s rho (r) between the role of cadres of elderly posyandu and the treatment of hypertension patients was 0.294 and p-value was 0.026 (p<0.05). Conclusion:It can be concluded that there was a positive and significant correlation between the role of cadres of elderly posyandu and the treatment of hypertension. Key word: Cadres, elderly posyandu, hypertension